Brugada pattern associated with febrile gastroenteritis: A case report - Edi, Larasati Cahyaning; Aminanto, Ahmad Ma'ruf Muttaqin; Paranita, Indah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
The Brugada pattern is an electrocardiographic manifestation that mimics true Brugada syndrome, potentially triggered by transient and reversible conditions. This case describes a 66-year-old Indonesian male with acute gastroenteritis, characterized by mild hypokalemia (3.2 mmol/L) and fever, who exhibited a Brugada type 1 ECG pattern. The patient experienced over 10 episodes of diarrhea, more than seven episodes of vomiting, and a fever of 39 °C, with no cardiac symptoms or family history of sudden cardiac death. The electrocardiogram (ECG) showed coved-type ST-segment elevation greater than 2 mm, accompanied by inverted T waves in leads V1-V3, which is indicative of a Brugada type 1 pattern. Laboratory results confirmed mild hypokalemia and leukocytosis, while echocardiography and chest X-ray showed no structural abnormalities. The patient received a comprehensive treatment plan including mineral sorbitol infusion, paracetamol, cefixime, potassium supplementation, and notably, cilostazol—a phosphodiesterase-3 inhibitor not previously documented for gastroenteritis-associated Brugada pattern. After three days of treatment, the Brugada pattern resolved. This case offers important insights for clinical practice in Indonesia by considering Brugada pattern in febrile gastroenteritis with ST-segment elevation, even with mild hypokalemia. It also raises the possibility that the combination of electrolyte correction and cilostazol may facilitate ECG normalisation. Further studies are needed to evaluate the therapeutic potential of cilostazol and to improve diagnostic accuracy in differentiating transient Brugada patterns from Brugada syndrome.